VD_FINDINFO Arrêt / 2023 / 503 vom 19. Juli 2023 - VD Tribunal cantonal (2023)
AA, INDEMNITÉ JOURNALIÈRE, SURASSURANCE, PERTE DE GAIN, REJET DE LA DEMANDE | 25 al. 1 LPGA, 68 LPGA, 69 LPGA, 51 al. 3 OLAA